New frontiers in agricultural history. Vol. 1 - Kauffman, Kyle Dean (Emerald, 2000)
This first volume in the series Advances in Agricultural Economic History, includes articles on the topics of Italian sharecropping, agricultural wage discrimination, factor endowment and contract choice, as well as new total factor productivity measures for the United States.
Keywords: Agriculture -- Economic aspects.; Agriculture -- History.; elektronické knihy; electronic books